(untitled) (Ágora de Heterodoxias, 2024)
Marian devotions have been studied from the aesthetic and architectural perspectives of the temples where homage is paid to the Virgin Mary. However, there is also a need for research that addresses socio-semiotic and iconic factors, as this would allow for a greater understanding of the elements, symbols, colors, and other representations present in these buildings. For this type of analysis, symbols, colors, and elements present in the buildings are considered, characteristics that define them and send messages to visitors. Thus, the corpus for analysis in this research will consist of 26 buildings that house the Marian Devotions in Latin America. The main theoretical references are Saussure, Verón, Pierce, and Panofsky. For the analysis, the following categories are considered: 1. Origin, country, location; 2. Religious manifestation; 3. Building, temple, sanctuary; 4. Image; 5. Festivity-celebration, as well as the iconic, aesthetic, symbolic elements, colors, and other notable representations in the mentioned buildings and what develops culturally around them, from a qualitative approach, with documentary analysis method with an emphasis on socio-semiotics, using the analysis matrix and descriptive sheets of the 26 considered buildings as instruments